간호대학생의 주관적 안녕감, 자아정체감, 가족기능과의 관계 - 김효정(Hyo-Jeong Kim) (한국콘텐츠학회 논문지, 14(2), 2014)
The aim of this study was to investigate the relationship among subjective well-being, self-identity and family function of nursing students. Descriptive study was conducted. The participants were 583 nursing students of three nursing colleges. Data were collected from the 1st of march 2011 to 31th of march in 2012 by using a structured questionnaire. The data were analyzed using SPSS/WIN 12.0 program. Subjective well-being showed significant differences according to gender, grade, religion, economic state, satisfaction of college life, major satisfaction and experienced clinical practice. Self-identity showed significant differences according to gender, religion, economic state, satisfaction of college life and major satisfaction. Family function showed significant differences according to economic state, major satisfaction. Subjective well-being self-identity, and family function are positive correlations each other. In conclusion, the program that consider nursing students' subjective well-being, self-identity and family function influences positive effect on the college life. 본 연구는 간호대학생의 주관적 안녕감과 자아정체감, 가족기능의 관계를 파악하고 고찰하기 위한 서술적 조사연구이다. 자료수집은 K, C도에 소재한 3개 대학에 재학 중인 583명을 대상으로 2011년 3월 1일부터 2012년 3월 31일까지 조사하였다. 수집된 자료는 SPSS 프로그램을 이용하여 백분율, 평균과 표준편차, t-test와 ANOVA, Pearson's correlation coefficients로 분석하였으며 연구결과는 다음과 같다. 본 연구결과 주관적 안녕감은 대상자의 일반적 특성 중 성별, 학년, 종교, 경제상태, 학교생활 만족도, 전공만족도, 임상실습 경험과 통계적으로 유의한 차이가 있었다. 자아정체감은 대상자의 일반적 특성 중 성별, 종교, 경제상태, 학업성적, 학교생활만족도, 전공만족도와 통계적으로 유의한 차이가 있었으며, 가족기능은 경제상태, 전공만족도와 통계적으로 유의한 차이가 있었다. 주관적 안녕감, 자아정체감, 가족기능은 서로 정적 상관관계가 있었다. 결론적으로 주관적 안녕감, 자아정체감, 가족기능을 고려한 프로그램은 간호대학생들의 대학생활에 긍정적으로 영향을 미칠 것으로 사료된다.